Applicability of Orem: training of caregiver of infant with Robin Sequence - Silva Demoro, Cleide Carolina da; Bertoncello Fontes, Cassiana Mendes [UNESP]; Trettene, Armando dos Santos; Cianciarullo, Tamara Iwanow; Lazarini, Ilza Marques (Assoc Brasileira Enfermagem, 2018)
Objective: to report the nurses' experience in relation to the training of caregivers of infants with Isolated Robin Sequence (IRS) for maintaining care after hospital discharge from the perspective of Self-Care Theoretical Framework. Method: the following categories were considered in this experience report: self-care action, self-care capacity, therapeutic self-care demand, self-care deficit, and nursing system. The nursing system was wholly compensatory and supportive-educative. Results: caregivers' training by nurses results in the acquisition of technical skills and specific knowledge related to the infant's positioning in elevated ventral decubitus, nasopharyngeal intubation, feeding-facilitating techniques and care with the feeding tube. Final considerations: the continuity of home care is guaranteed from caregivers' training for the therapeutic demand.
Keywords: Pediatric Nursing; Nurse; Self-Care; Caregiver; Pierre Robin Syndrome